2-[(Anilino)(2-nitrophenyl)methyl]cyclohexanone - Eftekhari-Sis, Bagher (International Union of Crystallography, 2012)
In the title compound, C(19)H(20)N(2)O(3), the cyclohexanone ring adopts a chair conformation with the aminomethyl group is positioned equatorially. An intramolecular N—H⋯O hydrogen bond occurs. In the crystal, molecules are linked by N—H⋯O hydrogen bonds.